Determine as raízes das equações abaixo:
a) x2 + 6x + 9 = 0
b) x² - 5x + 6 = 0
) ² −9 = 0
Soluções para a tarefa
Respondido por
1
a) Explicação: 11+6x=0
6x=-11
x=- 11/6
solução: x=- 11/6
B) explicação: x² - 5 x+6 =0
x²-2x - 3x+ =0
x x (x-2) - 3 ( x- 2) = 0
(x-2) x (x-3) = 0
x = 2
x = 3
solução = x¹ = 2, x ² = 3
Perguntas interessantes
Sociologia,
8 meses atrás
Matemática,
8 meses atrás
Ed. Física,
8 meses atrás
Matemática,
10 meses atrás
História,
10 meses atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás